Ethics in the conflicts of modernity an essay on desire, practical reasoning, and narrative - MacIntyre, Alasdair C. 1929-2025 (Cambridge University Press, 2020)
"This essay is divided into five chapters. In the first the questions initially posed about our desires and how we should think about them are questions that plain non philosophical persons often find themselves asking. When however they carry their attempt to answer these questions a little further, they find that they have, perhaps inadvertently, become philosophers, and that they need some at least of the conceptual and argumentative resources which professional philosophers provide. So their enquiry, like this one, becomes philosophical. But philosophy in our culture has become an almost exclusively specialized academic discipline whose practitioners for the most part address only each other rather than the educated lay person. Moreover those same practitioners have for the last fifty years been harassed by the academic system into publishing more and more as a condition for academic survival, so that on most topics of philosophical interest there is by now an increasingly large, an often unmanageable large body of literature that has to be read as a prologue before adding to it one more item. Readers should be warned that my references to this literature are selective and few. Had I conscientiously attempted not only to find my way through all the relevant published writing in the philosophy of mind and in ethics, but then also explained how I had come to terms with the claims advanced by its authors, I would have had to write at impossible length and in a format that would have made this essay inaccessible to the lay reader for whom it is written"...